ADJUVANT HORMONIOTHERAPY IN THE TREATMENT OF BREAST CANCER IN INITIAL STUDIES (CIPEEX, 2022)
BREAST CANCER IS THE SECOND MOST PREVALENT AMONG BRAZILIAN WOMEN. ITS PATHOPHYSIOLOGY IS RELATED TO THE ARCHITECTURE OF THE TUMOR CELL, SUCH AS THE TYPE OF HORMONE RECEPTOR EXPRESSED. IN THIS CONTEXT, ADJUVANT HORMONE THERAPY HAS BEEN SHOWING GOOD RESULTS IN THE TREATMENT OF ESTROGEN-POSITIVE BREAST CANCER. COMPARE THE DIFFERENT TYPES OF ADJUVANT HORMONE THERAPY IN EARLY ESTROGEN-POSITIVE BREAST CANCER. THIS IS AN INTEGRATIVE LITERATURE REVIEW WITH SEARCHES IN THE PUBMED AND LILACS DATABASES, FROM THE DESCRIPTORS INDEXED IN DECS: ENDOCRINE THERAPY; AROMATASE INHIBITOR; TAMOXIFEN; ADJUVANT THERAPY; BREAST CANCER PAPERS FROM 1989 TO 2018 AND ARTICLES RELEVANT TO THIS REVIEW WERE INCLUDED. IN TOTAL, 23 ARTICLES WERE INCLUDED IN THIS REVIEW. THREE GROUPS OF ADJUVANT HORMONE THERAPY WERE FOUND: USE OF ESTROGEN MODULATORS, AROMATASE INHIBITORS (AI) AND SUPPRESSION OF OVARIAN FUNCTION. ESTROGEN MODULATORS WERE REPRESENTED BY TAMOXIFEN. ITS TREATMENT PRESENTS GOOD RESULTS FOR THE PATIENT BY DECREASING MORBIMORTALITY, BUT HARMFUL ADVERSE EFFECTS TO THE PATIENT HAVE BEEN REPORTED, SUCH AS THROMBOEMBOLIC EPISODES AND INTIMA RELATIONSHIP WITH THE DEVELOPMENT OF ENDOMETRIAL CANCER. IN CONTRAST, AROMATASE INHIBITORS WERE RELATED TO BETTER SURVIVAL RATES WITHOUT THE DISEASE, AS WELL AS IMPROVED QUALITY OF LIFE DUE TO LOWER ADVERSE EFFECTS. OVARIAN SUPPRESSION, IN TURN, WAS AN INTERVENTION ASSOCIATED WITH THE OTHER 2 GROUPS, SO THAT THE ASSOCIATION BETWEEN AI AND OVARIAN SUPPRESSION OBTAINED THE BEST RESULTS IN RELATION TO PLACEBO AND TAMOXIFEN IN THE SURVIVAL CRITERIA WITHOUT THE DISEASE AND QUALITY OF LIFE. THE HORMONE THERAPY HAS UNDERGONE CHANGES WITH THE IMPROVEMENT OF THE QUALITY OF THE DRUGS, RESULTING IN A BETTER PROGNOSIS, BOTH IN THE LIFE OF THE PATIENT AND IN THE EVOLUTION OF THE PATHOLOGY. HOWEVER, THE DOCTOR MUST KNOW THE SINGULARITIES OF EACH PATIENT AND CHOOSE THE MOST APPROPRIATE INTERVENTION FOR EACH HEALTH-DISEASE PROCESS OF EACH PATIENT.
Keywords: Breast cancer. Estrogen receptor positive. Adjuvant hormone therapy.